Impact of losing and gaining streamflow conditions on hyporheic exchange fluxes induced by dune‐shaped bed forms. Issue 3 (6th March 2014) - Fox, Aryeh; Boano, Fulvio; Arnon, Shai
Abstract The exchange of water between the surface and subsurface environments plays a crucial role in hydrological, biogeochemical, and ecological processes. The exchange of water is driven by the local morphology of the streambed (hyporheic exchange) and the regional forcing of a large‐scale hydraulic gradient, which results in losing or gaining flow conditions. We measured the effects of losing and gaining flow conditions on hyporheic exchange fluxes in a sandy streambed using a novel laboratory flume system (640 cm long and 30 cm wide) under a combination of average overlying velocities and losing/gaining fluxes. Hyporheic exchange fluxes were analyzed based on a new conceptual framework. This combination of experimental observations and modeling revealed that hyporheic exchange fluxes under losing and gaining flow conditions are similar. Because interfacial transport increases proportionally to the square of the overlying velocity and linearly with increasing fluxes of losing and gaining conditions in the sand bed, the hyporheic exchange flux becomes smaller when the losing or gaining flux increases. Thus, losing and gaining flow conditions become the dominant mechanisms of water exchange at a certain flux, which depends on the competitive interaction between the overlying velocity in the stream and the losing/gaining fluxes.